Customer satisfaction towards the client's charter in Kajang Municipal Council - Munirah binti Salamat
This study analyzes the level of customer satisfaction among residents in Kajang, specifically customers of the Kajang Municipal Council (MPKj). It examines the respondents' orientation towards the Client's Charter and their level of satisfaction based on SERVQUAL dimensions. The administrative reform that took place in the 1990s has brought about significant changes in the administration system, particularly in Malaysia. 20 Development Administration Circulars have been issued in an effort to upgrade the quality of service within the public sector. Among the circulars are the principles of the Client's Charter. The introduction of the Client's Charter appears to be the best mechanism to change the quality of public service which has been frequently questioned by customers. The study is based on the findings of a questionnaire of which 200 copies were distributed to MPKj customers. The return rate was 84.5 %, meaning that 169 respondents responded to the questionnaire. The study found that the respondents have a medium level of satisfaction as; 49.7 % of them neither agreed nor disagreed in terms of the overall satisfaction regarding the services provided by the local government. The study concludes that there is a significant relationship between SERVQUAL dimensions as independent variables and satisfaction as a dependent variable. In short, an agency can be said to implement the Client's Charter successfully when it achieves a high level of customer satisfaction.